A novel testis-specific protein, PRAMEY, is involved in spermatogenesis in cattle. Issue 6 (June 2017) - Liu, Wan-Sheng; Zhao, Yaqi; Lu, Chen; Ning, Gang; Ma, Yun; Diaz, Francisco; O'Connor, Michael
Abstract : Preferentially expressed antigen in melanoma (PRAME) is a cancer/testis antigen that is predominantly expressed in normal testicular tissues and a variety of tumors. The function of the PRAME family in spermatogenesis remains unknown. This study was designed to characterize the Y-linked PRAME (PRAMEY) protein during spermatogenesis in cattle. We found that PRAMEY is a novel male germ cell-specific, and a germinal granule-associated protein that is expressed in spermatogenic cells during spermatogenesis. The intact PRAMEY protein (58 kDa) was detected in different ages of testes but not in epididymal spermatozoa. A PRAMEY isoform (30 kDa) was highly expressed only in testes after puberty and in epididymal spermatozoa. This isoform interacts with PP1γ2 and is likely the mature protein present in the testes and sperm. Immunofluorescent staining demonstrated that PRAMEY was located predominantly in the acrosome granule of spermatids, and in acrosome and flagellum of spermatozoa. Immunogold electron microscopy further localized the PRAMEY protein complex to the nucleus and several cytoplasmic organelles, including the rough endoplasmic reticulum, some small vesicles, the intermitochondrial cement, the chromatoid body and the centrioles, in spermatogonia, spermatocytes, spermatids and/or spermatozoa. PRAMEY was highly enriched in and structurally associated with the matrix of the acrosomal granule (AG) in round spermatids, and migrated with the expansion of the AG during acrosomal biogenesis. While the function of PRAMEY remains unclear during spermatogenesis, our results suggest that PRAMEY may play an essential role in acrosome biogenesis and spermatogenesis. Free Chinese abstract: A Chinese translation of this abstract is freely available athttp://www.reproduction-online.org/content/153/6/847/suppl/DC2 Spanish abstract: A Spanish translation of this abstract is freely available athttp://www.reproduction-online.org/content/153/6/847/suppl/DC3